Development of educational package and participatory consumer groups to improve food handling practices in food establishments in Sri Lanka - Lasantha Krishan Hirimuthugoda; Padmal De Silva; Palitha Abeykoon (SAGE Open Medicine, 2024)
Objectives: Improper food handling contributes to many foodborne diseases and food outbreaks globally leading to witnessed morbidities and mortalities. The study aims to develop an educational package and participatory consumer groups to improve food handling practices among food handlers and in food establishments in the Regional Director of Health Services area, Kalutara, Sri Lanka. Methods: The study developed an educational package and participatory consumer groups to improve the food handling practices among food handlers and in food establishments. The critical knowledge gaps were identified during the first component of this study, which was conducted as a descriptive study, and the findings were further discussed in the Focus Group Discussion. Posters, info sheets, and workshops were used for educational packages, and four consumer groups were formed. The second component of the study following the development of the interventions was continued as a three-arm, non-randomized controlled community trial for 4 months in the Regional Director of Health Services, Kalutara. Results: The educational package for food handlers was introduced as a package of a workshop, info sheets, posters to display at workplaces, and short refresher training two weekly to direct good food handling practices in food establishments. Consumer groups were strengthened to exercise their legal rights on their purchases and the ratings showed improvements in the hygiene levels with repeated consecutive visits. Conclusions: The novel educational package and participatory consumer groups are designed and implemented to improve food handling practices among food handlers and in food establishments.